A gas monitoring chamber for high pressure applications. (11th August 2021) - Hamacher-Baumann, P.; Roth, S.; Radermacher, T.; Thamm, N.
Abstract: Time Projection Chambers (TPCs) operated at high pressure have become a topic of interest for future long baseline neutrino experiments. Pressurized gas retains the low momentum threshold for particle detection of atmospheric TPCs, but offers a larger target mass for neutrino interactions at the same volume. Operation at high pressure poses several new challenges in safety aspects regarding overpressure and high voltage safety. The presented High Pressure Gas Monitoring Chamber (HPGMC) can be used to study the suitability of various drift gas mixtures up to 10 bar and a maximum field of ∼ 3000 V/cm. A flexible construction makes it possible to exchange parts of the inner detector and to test new technologies. In this work, the construction of a HPGMC and its commissioning using the P10 gas mixture (90 % Ar + 10 % CH4 ) are presented.